IoT-Enabled Dairy Systems: From Sensing and Data Integration to Operational Evaluation - Pipit Utami; Masduki Zakarijah; Mashoedah Mashoedah; Zidni Fikriawan; Nabila Yanti; Debora Aritonang; Gregoria Gendhis Pertiwi; Anafrio Rizqy Arba Pratama; Damarjati Azra (LPPJPHKI Universitas Dehasen Bengkulu, 2024)
The adoption of Internet of Things (IoT) technologies in dairy farming has expanded rapidly, yet the literature remains dominated by isolated technological components rather than operationally integrated systems. This study synthesizes research on IoT-based dairy farming systems through an end-to-end system perspective linking system purposes, sensing, data integration, intelligence, operational outputs, and evaluation. A systematic literature review was conducted on 38 Scopus-indexed articles published between 2020 and 2024 following the PRISMA protocol. The synthesis indicates that IoT applications are primarily oriented toward operational performance and initial quality indicators, barn environmental monitoring, animal health and welfare management, and operational efficiency and resource management. Although sensing technologies are relatively mature at the component level, most systems remain monitoring-oriented and support decision-making mainly through notifications and early warnings, with limited automation and operational evaluation. This review contributes a system-level conceptual framework that highlights the gap between technological capability and operational readiness, guiding the development of more coherent and operationally meaningful IoT applications in dairy farming.